Service survey: Old age care in five type municipalities 1993 - Strömberg, Lars; Nilsson, Lennart; Johansson, Vicki (University of Gothenburg, 1995)
This survey was carried out within the framework of the research programme ´Demokrati i förändring´. The survey was carried out in four municipalities; Grästorp, Kävlinge, Lidköping and Luleå, and in one district of Göteborg, Centrum. The choice of municipalities was made with regard to the classification of municipalities done in the citizen survey of the research programme, Local citizen survey 1991 (SSD 0306). The survey was directed towards persons aged 65-85. The questionnaire contained questions about marital status; size of household; number of sons and daughters; distance to children´s home; how often one sees the children or speaks with them on the telephone; opinion on how public old-age care ought to be worked out; economic aid to alternative old-age care; economic aid to elderly. For some twenty areas the respondents had to state if they took care of them themselves or if they were assisted by someone; if they were assisted by home-help; at what time they were assisted by someone else; opinion on the public old-age care; and monthly cost for old-age care. A number of questions dealt with attitude towards the public old-age care and its personnel; opinion of the assistance in general, if one needs more assistance and from whom one would like assistance; distribution of old-age care between various groups of elderly, and under what circumstances one is prepared to pay for old-age care. The questionnaire also included questions on how often the respondent, and spouse if any, used medical care and transportation service during the last six months; opinion of the distribution of medical care between various groups; and under what circumstances one is prepared to pay for medical care. The respondents also had to state their opinion on local authority services in various areas; service areas most important to focus on and service areas possible to cut down; opinion on local authority service in general; and experience of their own contacts with local government officers within the old-age care department. Furthermore the respondents had to declare if they agreed or not in a number of statements about local authority services and taxes.

Denna studie har genomförts inom ramen för det statsvetenskapliga disciplinprogrammet 'Demokrati i förändring'. Undersökningen genomfördes i de fyra kommunerna Grästorp, Kävlinge, Lidköping och Luleå samt i stadsdelen Centrum i Göteborg. Valet av kommuner har gjorts med utgångspunkt från den kommungruppsindelning som gjordes för programmets medborgarundersökning, Kommunmedborgarundersökningen 1991 (SSD 0306).
Undersökningen riktade sig till personer i åldrarna 65-85 år och formuläret innehöll frågor om civilstånd; hushållets storlek; antal söner och döttrar; avstånd till barnens bostad; hur ofta man träffar barnen eller talar i telefon med dem; inställning till hur kommunens äldreomsorg bör utformas; stöd till alternativ äldreomsorg; utformning av stöd till äldre. Respondenterna fick för ett tjugotal områden ange om man skötte dessa själva eller fick hjälp av någon; om man får hjälp från kommunens hemvård; under vilken tid man får hjälp av någon annan; hur man tycker kommunens hemvård fungerar och hur mycket man betalar per månad. Ett antal frågor berörde inställningen till hemvården och dess personal; hur man tycker hjälpen fungerar som helhet; om man behöver ytterligare hjälp och av vem man skulle vilja ha hjälp; fördelningen av äldreomsorgen mellan olika äldregrupper; och under vilka omständigheter man är beredd att betala för äldreomsorgen. Enkäten innehöll även frågor om hur ofta respondenten och eventuell partner använt sig av sjukvård och färdtjänst under senaste halvåret, inställning till sjukvårdens fördelning mellan olika grupper och under vilka omständigheter man är beredd att betala för sjukvård. Respondenten fick även ange vilken inställning man har till kommunens service på olika områden; vilka områden det är mest angeläget att satsa på och vilka serviceområden man i första hand kan minska på; inställning till den kommunala servicen totalt; samt hur man upplevde sina egna kontakter med tjänstemännen inom äldreomsorgen. Därutöver fick man ange om man instämde eller ej i ett antal påståenden om servicen och skatten.
Serviceundersökningen: Äldreomsorg i fem typkommuner 1993
Keywords: care of the elderly; äldreomsorg; old age; ålderdom; social welfare; social välfärd; Housing for the Elderly; Äldreboende; local government services; kommunal service; medical care; sjukvård; social security; social trygghet; welfare policy; social- och välfärdspolitik; General health and well-being; Allmän hälsa och välbefinnande; Family life and marriage; Familjeliv och äktenskap; Elderly; Äldre; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap